The role of the sports media in the visual cognitive and cultural aspect of the coaches of the Iraqi Premier League football - Ali, Suha; Raisan, Fadhil (Journal of Physical Education, 2015)
The media according to its means , including the media visible athlete ’s keenness to provide a number of sports material to support what is the concept of physical activity , including the promotion of key aspects of the experiences of the training , which the researcher considers it to be straightened by ( coaches the Iraqi Premier League football ) different segments in order his interest in this subject and makes it a place of his research and follow-up for the development of vocabulary , consistent with the need , and for this important study will researcher ( enhance the training experience for trainers of the Iraqi Premier League football exposure Media Sports video ) to see the nature of the relationshipBetween the sports media and visual impact on the trainers , to act as an incentive to correct the kinks during competitions excellent ball League , as well as promoting the positive cases and fault diagnosis for the development of effective solutions through theoretical and practical analysis , it gives the chance for coaches to review all the plans and strategies that have been developed such as the start of the league after the end of each stage of the local tournament